2022
DOI: 10.1007/s11071-022-07779-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact energy and the risk of injury to motorcar occupants in the front-to-side vehicle collision

Abstract: The effects of a road accident where one vehicle hits its front on the side of another one are explored. In such cases, the impacted vehicle’s side is usually significantly deformed, which causes a risk of serious injury to vehicle occupants. An analysis of the front-to-side collision covers many nonlinear and highly complex processes, especially when it is based on the collision energy balance. For the analysis, a model of a front-to-side motorcar collision and a dummy representing the impacted vehicle’s driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Research has found that left OOP reduces the severity of driver injuries, Xu Zhe [11] studied the forward disengagement of occupants caused by the AEB system, and Mages [16] showed that this disengagement increases occupant injuries, so we believe that excessive disengagement will cause the driver to come into contact with the door or the B-pillar, which will increase the risk of driver injuries, and that, in addition to the improvement of the AES system, it is necessary to match the active pre-tensioning seat belts with the side airbags to protect the driver; More serious damage occurred when the collision area was the B-pillar, and Leon [28] also indicated that contact with the B-pillar caused the most serious damage in a side impact; At impact angle of 60°, the abdominal combined force was found to exceed the threshold and the severity of injury was higher, so we suggest that improvements to the AES need to be made to avoid the B-pillar and impact angles of 60° as much as possible. With active pre-tensioning seat belts, lateral OOP of all parts of the driver was reduced, and driver injuries were reduced compared to normal seat belts.…”
Section: Ivdiscussionmentioning
confidence: 99%
“…Research has found that left OOP reduces the severity of driver injuries, Xu Zhe [11] studied the forward disengagement of occupants caused by the AEB system, and Mages [16] showed that this disengagement increases occupant injuries, so we believe that excessive disengagement will cause the driver to come into contact with the door or the B-pillar, which will increase the risk of driver injuries, and that, in addition to the improvement of the AES system, it is necessary to match the active pre-tensioning seat belts with the side airbags to protect the driver; More serious damage occurred when the collision area was the B-pillar, and Leon [28] also indicated that contact with the B-pillar caused the most serious damage in a side impact; At impact angle of 60°, the abdominal combined force was found to exceed the threshold and the severity of injury was higher, so we suggest that improvements to the AES need to be made to avoid the B-pillar and impact angles of 60° as much as possible. With active pre-tensioning seat belts, lateral OOP of all parts of the driver was reduced, and driver injuries were reduced compared to normal seat belts.…”
Section: Ivdiscussionmentioning
confidence: 99%
“…In the first phase of motion, the car has moved with relative transverse friction between the tires and the road surface, and the motion trajectory is arc-shaped. The car has crossed the entire traffic lane diagonally and what follows is an impact into the roadside tree (Figures 1 and 2) [13][14][15][16]. of mass of the car coordinate system, symmetrically located with respect to the car body.…”
Section: Dynamic Model Of a Vehicle-fixed Barrier Front Crashmentioning
confidence: 99%
“…In the first phase of motion, the car has moved with relative transverse friction between the tires and the road surface, and the motion trajectory is arc-shaped. The car has crossed the entire traffic lane diagonally and what follows is an impact into the roadside tree (Figures 1 and 2) [13][14][15][16]. As long as the kinematic quantities in the motion phases are known, it would be possible to sufficiently predict the magnitudes and directions of each component of the inertial forces, including the magnitude of the resultant vector sum.…”
Section: Dynamic Model Of a Vehicle-fixed Barrier Front Crashmentioning
confidence: 99%
“…The crashworthiness requirements mainly involved about 44 rules in FAR 25, and were mainly distributed in subparts C, D, E, F and G [32][33][34], such as Section 25.561 "General" and Section 25.562 "Emergency landing dynamic conditions", which emphasizing that the aircraft structure design must protect each occupant during an emergency landing condition, and provide the dynamic conditions for the seat design. Many impact sled tests had been conducted to evaluate the occupant injury, and many correlated studies of analytical simulations with impact sled test results had also been accomplished [35][36][37]. Therefore, a series of guidance documents had been formed for the verification and certification of aircraft crashworthiness and occupant safety.…”
Section: Introductionmentioning
confidence: 99%